Bridging Gaps in Students’ Numeracy and Critical Thinking: Is Wayground the Future of Interactive Digital Learning? - Zamratul Aswad; Mahsup; Abdillah; Syaharuddin; Wasim Raza (Journal of Education Reseach and Evaluation, 2026)
The fundamental problem in mathematics learning is the low level of critical thinking and mathematical numeracy skills among students, caused by teacher-centered learning and limited use of interactive learning media that support independent exploration and understanding of concepts. Based on these problems, this study aims to analyze the effectiveness of Wayground interactive digital media in improving students' critical thinking and mathematical numeracy skills. This study is a quantitative study with a quasi-experimental design using a pretest–posttest control group model. The research subjects involved 54 ninth-grade students as samples, divided into an experimental class (27 students) and a control class (27 students). Data collection was conducted through tests and questionnaires, with instruments in the form of critical thinking and mathematical numeracy tests and a Likert-scale student perception questionnaire. The data obtained were analyzed using the Shapiro–Wilk normality test, Levene's homogeneity test, paired sample t-test, independent sample t-test, as well as learning improvement analysis through N-Gain and effect size. The results showed that the use of Wayground interactive digital media provided a more optimal improvement in critical thinking and mathematical numeracy skills compared to conventional learning, with a high improvement category in the experimental class and a moderate improvement in the control class. Based on these findings, it can be concluded that Wayground interactive digital media is effective in mathematics learning and has important implications as an innovative, interactive, and applicable learning media alternative to support the development of students' higher-order thinking skills.